ISOTOPIC SIGNATURES AND ORIGIN OF NITROGEN IN IIE AND IVA IRON METEORITES - Mathew K.J.; Palma R.L.; Marti K.; Lavielle B. (My University, 2000)
Nitrogen concentrations and isotopic signatures have been determined in groups IIE and IVA iron meteorites. Contrary to assumptions made in the literature, the present data show that spallation components significantly modify the N signatures of the metal. All 15N data are corrected for cosmic-ray produced spallation components using 21Ne concentrations measured in aliquots. A production-rate ratio 21Ne/15N = 0.80 is obtained, which can reliably be used for this correction, since it is not sensitive to shielding differences. The trapped N signatures in group IVA irons fall into two subgroups IVA (−26) with δ15N = −26 ± 2 ‰ and IVA (−6) with δ15N = −6 ± 1.4‰, respectively. Only the latter is close to values reported for metal of L-chondrites. Group IIE irons also define two distinct subgroups IIE (Y) with δ15N = −7.5 ± 1.5‰ and IIE (O) with δ15N = −2.3 ± 1‰. Therefore, the earlier proposed subdivision of IIE irons into “young” and “old” subgroups is substantiated by the different trapped N signatures. With regard to a possible relationship with H-chondrites as suggested by oxygen isotopes, only the young IIE subgroup overlaps the range of signatures reported in H-chondrite metal. Seymchan has a distinctly lighter signature (δ15N = −54‰), consistent with its reclassification as an ungrouped iron. We observe no correlation of either nitrogen concentrations or isotopic signatures with abundances of Ga, Ge, Ir or Ni. The distinct N components in the so-called magmatic group IVA constrain the thermal history of the parent body, as these signatures need to be reconciled with the magmatic history. Implications for the origin of nitrogen components are discussed. Some of the spread in N isotopic data in the literature apparently is due to inclusions.